Lattice Boltzmann simulation of droplet impact on orifice plate with different wettability. (15th November 2022) - Liang, Jia; Gao, Ming; Chen, Lu; Wang, Dongmin; Wang, Zhiyun
Highlights: Dynamic behavior of droplet impacting on the surface of hydrophilic and hydrophobic orifices was studied. There is a critical W e number for droplet passing through the orifice plate. A W e- Oh map was obtained, used for predict droplet breakup. Two states modes were found when droplet passing through orifice plate: creep pattern and quick pattern. The hydrophobic orifice plate presents four modes and the hydrophilic orifice plate presents five modes when droplet impacts the orifice plate. Abstract: In this paper, simulation results of droplet impact motion on hydrophilic ( θ =80°) and hydrophobic ( θ =160°) orifice surfaces are obtained by a single component multiphase lattice Boltzmann model (LBM). And a piecewise relaxation time is used to improve the numerical stability under high liquid/vapor density and low droplet viscosity. The effects of Weber ( We ) number, Ohnesorge ( Oh ) number, orifice thickness, and the diameter ratio of the orifice and droplet on the deformation process of the droplet impact on hydrophilic and hydrophobic orifice plates were studied, including the phenomena of liquid slug and breakage. As a result, at a low We number, the droplet is not easy to pass through the orifice, and the liquid plug phenomenon will be formed in the hydrophilic orifice, which is because of the hydrophilic effect on the orifice surface forms capillary action. At a high We number, the droplet will break when it impacts the orifice plate. In addition, the critical We number of droplets passing through the surface of a hydrophilic orifice has a linear relationship with the thickness of the orifice, while there is a critical We number of droplets passing through the surface of a hydrophobic orifice, which corresponds to two different forms of passage: peristaltic form and rapid through the form. The state diagram of the droplet with different We number, orifice diameter and droplet diameter ratio is obtained, which can be used to predict the different states of the droplet after impacting the orifice. According to the We number and Oh number, a graph for predicting droplet rupture is obtained. The critical We number increases with the increase of The Oh number, which means that the more viscous droplet requires a larger We number to rupture.